Films Of P. Ramlee : An Analysis Of Sexual Politics And Social Class Conflicts - Ooi, Chia-Yi (2012)
This thesis strives to achieve two major goals. One is to increase the knowledge on the understanding of sexual politics in gender discrimination towards women. Secondly, is to examine the conflict of the division of class in Malaysian society highlighted in the moving images and texts of the six chosen P. Ramlee’s melodramas. The analyses of these six films were according to the structure of both textual and narrative analysis methods; which provides the analytical principles to illustrate the functionality and applicability of the feminist film theory of psychoanalysis and Marxist class conflict approach to film.